The Effectiveness of PowToon Towards Junior High School Students’ Reading Skills - Ni Luh Putu Niken Apsari; Made Hery Santosa; Kadek Sintya Dewi (Universitas Muhammadiyah Kalimantan Timur, 2023)
The purpose of this study is to investigate the effectiveness of using PowToon toward junior high school students’ reading skills. The quantitative method with a quasi-experimental posttest only control group design. The data was analyzed using statistical and inferential analysis through SPSS to get the score. Therefore, the student’s score was used to compare those two groups’ reading skills. The sample of this study was 80 students at SMPN 4 Singaraja who were divided into two groups within one group consisting of 40 students. The collection of data was being collected through a post-test. The result of the study showed that the score of the group who received treatment in this study had significant differences compared with the group who did not use PowToon in the learning process. Furthermore, the data collection was tested using an independent sample t-test in order to know whether the use of PowToon has a significant effect or not. After conducting the test, the result showed that the sig. (2-tailed) was smaller than the alpha level (α = 0.05) in which the result of the test was sig. (2-tailed) 0.000. It can indicate that a significant effect related to the use of PowToon can help the students affect their reading skills. In addition, the use of PowToon was highly recommended use in affecting the students’ reading skills because it has a significant effect on the students and also this tool can make the activity of the learning process be more efficient, entertaining, interesting, and enjoyable.